INTERNALISASI AJARAN ISLAM MELALUI LAYANAN KONSELING DAN TERAPI BAGI WARGA BINAAN RUMAH TAHANAN NEGARA KELAS II B ANAK AIR PADANG - Zuwirda Zuwirda; Eliza Eliza; Nazirman Nazirman (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The Community Service Program of UIN Imam Bonjol Padang is a concrete implementation of scientific and religious studies organized by the academic community of UIN Imam Bonjol Padang for the Community. In the process of community service carried out by lecturers in coordination of LP2M and the Faculty of Da'wah and Communication Sciences of UIN Imam Bonjol Padang in 2017. So the group of lecturers of Islamic Counseling Guidance held community service activities with the title